The CLE gene family in Populus trichocarpa. (2nd June 2016) - Liu, Zhijun; Yang, Nan; Lv, Yanting; Pan, Lixia; Lv, Shuo; Han, Huibin; Wang, Guodong
ABSTRACT: The CLE (CLAVATA3/Embryo Surrounding Region-related) peptides are small secreted signaling peptides that are primarily involved in the regulation of stem cell homeostasis in different plant meristems. Particularly, the characterization of the CLE41-PXY/TDR signaling pathway has greatly advanced our understanding on the potential roles of CLE peptides in vascular development and wood formation. Nevertheless, our knowledge on this gene family in a tree species is limited. In a recent study, we reported on a systematically investigation of the CLE gene family in Populus trichocarpa . The potential roles of PtCLE genes were studied by comparative analysis and transcriptional profiling. Among fifty PtCLE members, many PtCLE proteins share identical CLE motifs or contain the same CLE motif as that of AtCLEs, while PtCLE genes exhibited either comparable or distinct expression patterns comparing to their Arabidopsis counterparts. These findings indicate the existence of both functional conservation and functional divergence between PtCLEs and their AtCLE orthologues. Our results provide valuable resources for future functional investigations of these critical signaling molecules in woody plants.